Eating behavior and obesity : behavioral economics strategies for health professionals - Heshmat, Shahram (Springer Pub. Co., 2011)
Obesity is one of the most pressing health issues affecting our country. This unique volume is the first to apply behavioral economics-the integration of psychological and economic knowledge-to the study of eating behavior. The text demonstrates how this discipline can be used to understand why it so difficult for individuals to control their eating habits, and helps readers use this knowledge to create and improve public health nutrition programs and policies. The text examines dietary choices and obesity through a multidisciplinary lens of biological, psychological, and social factors, and d.